2017
DOI: 10.1111/jfb.13457
|View full text |Cite
|
Sign up to set email alerts
|

Using the robust design framework and relative abundance to predict the population size of pallid sturgeon Scaphirhynchus albus in the lower Missouri River

Abstract: Several population viability models were constructed to aid recovery in endangered Scaphirhynchus albus, but these models are dependent upon accurate and precise input parameters that are not provided with standard catch per unit effort (CPUE) indices. Nine years of sampling efforts, under the robust design framework, provided 1223 unique captures with an 18·3% recapture rate. The annual population estimates varied from 4·0-7·3 fish rkm for wild and 8·4-18·4 fish rkm for hatchery-reared S. albus. The relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The pallid sturgeon Augmentation Program has increased the overall pallid sturgeon population in the lower Missouri River. Steffensen, Powell, and Pegg () predicted the current pallid sturgeon population in the lower Missouri River at approximately 13,616 ( SE ± 7,142) fish in 2015; whereas comparatively, Wu and Halon () estimated the entire pallid sturgeon population at 5,655 (95% CI = 4,273–7,572) using data from 2006 to 2010. Both these population estimates combined wild‐origin and hatchery‐reared, but Steffensen, Pegg, and Mestl () reported that hatchery‐reared fish were captured at a much higher frequency ranging from 3.5 to 5.9:1 wild‐origin fish.…”
Section: Discussionmentioning
confidence: 99%
“…The pallid sturgeon Augmentation Program has increased the overall pallid sturgeon population in the lower Missouri River. Steffensen, Powell, and Pegg () predicted the current pallid sturgeon population in the lower Missouri River at approximately 13,616 ( SE ± 7,142) fish in 2015; whereas comparatively, Wu and Halon () estimated the entire pallid sturgeon population at 5,655 (95% CI = 4,273–7,572) using data from 2006 to 2010. Both these population estimates combined wild‐origin and hatchery‐reared, but Steffensen, Pegg, and Mestl () reported that hatchery‐reared fish were captured at a much higher frequency ranging from 3.5 to 5.9:1 wild‐origin fish.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers utilized data collected by the Pallid Sturgeon Population Assessment Project (PSPAP) and targeted broodstock collection activities from 2003 to 2015 Steffensen et al 2017; Data S1, Supplemental Material). Sampling occurred in the main-stem Missouri River downstream of Gavins Point Dam (rkm 1,305.1) to the confluence of the Missouri and Mississippi rivers (rkm 0.0) and lower reaches of the major tributaries, including the James, Big Sioux, Platte, Kansas, Grand, and Osage rivers ( Figure 1).…”
Section: Sampling Methodsmentioning
confidence: 99%
“…Researchers used common handling protocols throughout the Missouri River basin; these included a suite of gears that effectively captured all size classes of Pallid Sturgeon Steffensen et al 2017). All collection efforts conformed to the USFWS Pallid Sturgeon Handling Protocols and were permitted under USFWS handling permits.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…Since 2003, NGPC has been a participating agency in the Pallid Sturgeon Population Assessment Program (PS-PAP), which is the main Pallid Sturgeon monitoring program on the Missouri River which monitors the relative abundance of benthic fish species with a suite of gears . Additionally in early-April 2008 through 2017, NGPC has conducted an intensive sampling effort to collect adult Pallid Sturgeon for the lower Missouri River Supplementation Program (Steffensen et al 2017b). These reproductively ready adult fish are transferred and spawned at hatchery facilities to provide progeny to supplement the Pallid Sturgeon population.…”
Section: Capture Informationmentioning
confidence: 99%
“…Steffensen and Mestl (2016) hypothesized the poor condition recently observed has caused Pallid Sturgeon to limit the frequency of becoming reproductively ready and possibly delay sexual maturation. More concerning, Pallid Sturgeon capture research article rates and population estimates have declined, despite the ongoing Supplementation Program (Steffensen et al 2017b), which may indicate increased mortality rates or higher rates of emigration from the lower Missouri River. However, evidence of increased emigration is lacking as Pallid Sturgeon capture frequencies are not increasing in other reaches of the lower Missouri River (K. Steffensen, unpublished data).…”
Section: Introductionmentioning
confidence: 99%